What are the key drivers of customers loyalty in yogurts' category?: a case study of Pingo Doce - Guerreiro, Carolina Vasconcelos Marcelino Loia (2019)
What influences customers behavior? How do they become loyal to a certain supermarket or product? One key element of understanding and managing customer experience is the ability to measure and monitor customer reactions to firm offerings, especially customer attitudes and perceptions. Nowadays customers have more expectations about what they want to. They expect experiences in which they are involve to. There is an increasing desire for multiplicity and experiences are expected to offer more. Consumers are rejecting, the idea of passive on looking, they desire now active participation. In a fast-changing world, customer buying decision-making processes become an important topic to understand. In order to be successful and "to catch" more loyal customers it is relevant to understand their experience and behavior. Customer's loyalty is one of the aims that a supermarket wants to achieve. When predicting consumer's behavior, they can use it in their own profit. If they know in advance what specific products do customers look for, they can use marketing and some other strategies to push them to purchase it. This way they can be one step ahead and act in an effective and efficient way. This research seeks to understand the main variables that influences customer loyalty in Pingo Doce yogurt's category.